Foreign experience in the development of entrepreneurial ecosystems and the possibility of its application in Russia - T. G. Antropova; M. V. Shatokhin; N. M. Suray (Омский научный вестник: Серия "Общество. История. Современность")
At the heart of this study is the importance of understanding the role of the entrepreneurial ecosystem in the context of an ever-changing global economy. Researchers’ interest in conceptualizing entrepreneurial ecosystems has begun to emerge in the last two decades. They are able to identify the key factors for a successful entrepreneurial ecosystem by drawing analogies to natural ecosystems. The study summarizes the most important research findings in this area, summarizing the key factors necessary for an ecosystem to be considered entrepreneurial, with significant economic, technological and social impact. The object of the study is the entrepreneurial ecosystem, which is considered as a complex system consisting of various interconnected elements, including entrepreneurs, investors, mentors, educational institutions and government agencies. This study provides an overview of the entrepreneurial ecosystems of the world’s leading economies to identify their key characteristics and strengths. The structural elements, support mechanisms, and cultural factors that shape and differentiate these ecosystems are examined. The review aims to provide information that may be useful to policymakers, businesses and stakeholders. The goal is to, by understanding the nuances of each ecosystem, identify transferable best practices, promote cross-cultural collaboration, and contribute to a more sustainable and competitive domestic business environment. This review highlights the different characteristics of entrepreneurial ecosystems in India, the US and China to understand the intricacies that drive innovation and economic growth. As the global landscape continues to evolve, this review serves as a valuable resource for shaping policy, strengthening collaboration, and deepening the collective understanding of what facilitates successful entrepreneurship in diverse and dynamic contexts.